Determinants of fatigue in children and adolescents with type 1 diabetes mellitus: A systematic review - Ningsih, Risna; Islamia, Ina; Agustini, Nur; Ramadhani, Dewi Astika; Adawiyah, Robiyatul; Huda, Mega Hasanul; Hayati, Dewi (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Fatigue is one of the most common non-specific symptoms experienced by children and adolescents with type 1 diabetes mellitus (T1DM), yet it often goes unnoticed by clinicians. It can affect quality of life, learning ability, and engagement in daily activities. Fatigue in T1DM patients is not only related to glycemic control, but is also influenced by a complex range of physical, psychological and social determinants. A comprehensive understanding of the factors that contribute to fatigue in this population is essential for the development of more effective and holistic intervention strategies. Purpose: To determine fatigue among children and adolescents with Type 1 Diabetes Mellitus. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The article search was conducted systematically using the keywords: “Child” AND “Children” AND “Adolescent” AND “Adolescence” AND “Teenagers” AND “Diabetes Mellitus Type 1” AND “Type 1 Diabetes” AND “IDDM” AND “Type 1 Diabetes Mellitus” AND “Juvenile Onset Diabetes” AND “Psychosocial Problem” AND “Psychosocial Support System” AND “Psychological Support System” AND “Social Support System”. This study is registered on PROSPERO (CRD42024618445). Results: Aside from anxiety, depression, and behavioral disorders, other psychosocial issues—specifically self-management difficulties—are also observed in children with T1DM. These challenges are often associated with fatigue, which can negatively affect a child's motivation, focus, and ability to consistently carry out essential diabetes care tasks such as taking insulin, monitoring blood sugar levels, managing diet, and engaging in physical activity. Conclusion: The findings related to fatigue as a psychosocial issue may offer evidence-based support for the early identification and intervention of psychosocial challenges in children and adolescents with T1DM.